2021
DOI: 10.14254/2071-789x.2021/14-4/14
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to understanding migration: A multi-country analysis of the push and pull migration trend

Abstract: The study explores the factors that drive migration to Poland and Thailand. It investigated how economic, political, environmental, and social factors impact on workers decision to migrate in search of greener pastures. The research is hinged on the Push-Pull Migration Model. The research populations consisted of a total of 762 purposively selected respondents; 452 were selected from Bangkok and Phuket, Thailand, while 310 were selected from Warsaw in Poland. The study was quantitative research that applied SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 51 publications
(73 reference statements)
2
19
0
Order By: Relevance
“…Dhir and Dutta (2020) asserted that inadequate quality of worklife experienced by physicians and other healthcare workers leads to mistakes at work, accidents and job dissatisfaction among employees in hospitals surveyed recently. The discovery of Khalid and Urbanski (2021), whose study showed that employees' inadequate quality of life pushed many outside the country, is worthy of note. In other words, the lack of quality of worklife among the physicians enabled them to support brain-drain syndrome and search for a better work environment where their expertise will be appreciated and valued.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Dhir and Dutta (2020) asserted that inadequate quality of worklife experienced by physicians and other healthcare workers leads to mistakes at work, accidents and job dissatisfaction among employees in hospitals surveyed recently. The discovery of Khalid and Urbanski (2021), whose study showed that employees' inadequate quality of life pushed many outside the country, is worthy of note. In other words, the lack of quality of worklife among the physicians enabled them to support brain-drain syndrome and search for a better work environment where their expertise will be appreciated and valued.…”
Section: Review Of Literaturementioning
confidence: 99%
“…persecution) that repel individuals from an area and attract them to another location (e.g. job opportunities) (Khalid and Urbański 2021). We focus specifically on push factors and how they relate to migration, as well as to other push factors.…”
Section: Conceptualising the Complexities Of Climate Migrationmentioning
confidence: 99%
“…In addition, migration leads to the phenomenon of the so-called brain drain (Mountford, 1997, Borjas, 2000, OECD, 2017b in the case of skilled, trained and educated people, which, in the long-term view, limits the growth potential of source economies. Furthermore, skilled migrants often choose the developed countries for migration considering the possibilities for work and professional development as one of the pull factors, so, they additionally strengthen the prerequisites for the economic development of the recipient countries (Oliinyk et al, 2022;Khalid & Urbański, 2021).…”
Section: Introductionmentioning
confidence: 99%